Energy Metabolism Regulates Stem Cell Pluripotency - Tsogtbaatar, Enkhtuul; Landin, Chelsea; Minter-Dykhouse, Katherine; Folmes, Clifford D. L. (Frontiers in Cell and Developmental Biology, 2020)
Pluripotent stem cells (PSCs) are characterized by their unique capacity for both unlimited self-renewal and their potential to differentiate to all cell lineages contained within the three primary germ layers. While once considered a distinct cellular state, it is becoming clear that pluripotency is in fact a continuum of cellular states, all capable of self-renewal and differentiation, yet with distinct metabolic, mitochondrial and epigenetic features dependent on gestational stage. In this review we focus on two of the most clearly defined states: “naïve” and “primed” pluripotent stem cells (PSCs). Like other rapidly dividing cells, PSCs have a high demand for anabolic precursors necessary to replicate their genome, cytoplasm and organelles, while concurrently consuming energy in the form of ATP. This requirement for both anabolic and catabolic processes sufficient to supply a highly adapted cell cycle in the context of reduced oxygen availability, distinguishes PSCs from their differentiated progeny, and from tumor cells. During early embryogenesis PSCs adapt their substrate preference to match their anabolic and energetic requirements with that of the developmental process. This is reflected in different mitochondrial morphologies, membrane potentials and electron transport chain compositions, and utilization of glycolysis. Additionally, metabolites produced in PSCs can directly influence epigenetic and transcriptional programs, which in turn can affect self-renewal characteristics. Thus, our understanding of the role of metabolism in PSC fate has expanded from anabolism and catabolism to include governance of the pluripotent epigenetic landscape. Understanding the roles of metabolism and the factors influencing metabolic pathways in naïve and primed pluripotent states provide a platform for understanding the drivers of cell fate during development. This review highlights the roles of the major metabolic pathways in the acquisition and maintenance of the different states of pluripotency.